2014
DOI: 10.4103/2141-9248.144909
|View full text |Cite
|
Sign up to set email alerts
|

Emergency contraception: Awareness, perception and practice among female undergraduates in imo state university, southeastern Nigeria

Abstract: Background:Limited knowledge and practice of contraception is a global public health problem. Unintended pregnancies are the primary cause of induced abortion. When safe abortions are not available, as in Nigeria with restricted abortion laws, abortion can contribute significantly to maternal mortality and morbidity. Adequate information on the awareness and the use of emergency contraception is necessary for planning interventions in groups vulnerable to unwanted pregnancy.Aim:The aim of the following study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…These findings of this study indicated that the knowledge and awareness of birth control of pharmacy students at LHU were lower than the rates reported in other studies in Malaysia, [14] Nigeria, [23,24] and South Africa. [25] However, increasing levels of awareness can be attributed to the increasing use of social networks/media, which was identified as one of the main sources of knowledge in this study.…”
Section: Discussioncontrasting
confidence: 83%
“…These findings of this study indicated that the knowledge and awareness of birth control of pharmacy students at LHU were lower than the rates reported in other studies in Malaysia, [14] Nigeria, [23,24] and South Africa. [25] However, increasing levels of awareness can be attributed to the increasing use of social networks/media, which was identified as one of the main sources of knowledge in this study.…”
Section: Discussioncontrasting
confidence: 83%
“…Inclusion of reproductive health education as part of the school curriculum might help to change the attitude. 20 Couples should be encouraged to use regular and emergency contraceptive to reduce induced abortions, both legal and illegal. 21 This can be achieved by providing information about the available contraceptive methods and helping couples to choose what suits them.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the deaths that occur in developing countries are due to the lack of accessibility and availability of reproductive health services, especially family planning. Utilization of emergency contraceptive may play vital role in decreasing abortion and its complications [13].…”
Section: Introductionmentioning
confidence: 99%